Analisis Penerapan Proteksi Kebakaran (APAR) di Dinas kesehatan Inhil Tahun 2021 - Puspa Maria; Kamali Zaman; Rahmi Indrasuri (Universitas Batanghari Jambi, 2022)
Fires are an event that can occur anywhere in forests, land, settlements and buildings whose incident cannot be expected and predictable. As a means of rescue if a fire occurs is a light fire extinguisher, emergency ladder, and an emergency door. APAR use is one way to prevent and overcome fire so that it is no bigger that causes losses even casualties. To identify and make countermeasures on the source of hazard in the work environment. This research method is to give qualitative research with the design of Rappid Assessment Procedure. Data collection is done by observation, direct interviews and audit documents. To set priority problems using the brainstorming method and determination of alternative problem solving using fish bone analysis and matrix intervention plan. The results of the identification of the problem are the unavailability of appars in the Indragiri Hilir District Health Office. The problems obtained are the existence of APAR installation in the Inhil Health Office Building, lack of knowledge of legislation on fire protection systems, the incomplete equipment for fire protection systems, and funding obtained is not enough to budget the purchase of APAR.